Study of the Efficacy of Acupuncture on the Vital Signs, Hematology and some Biochemical Parameters in Arabian Horses (Journal of Hama University, 2022)
The research was conducted on 24 healthy Arabian horses, from equestrian clubs and private stables in the governorates of Homs, Hama, and Damascus countryside between January and September of 2021.The horses were subjected to a dry-needling and an aqua-acupuncture technique through the acupoints map for /30/ minutes session. This was done to record and study the variables outcome from acupuncture at the level of vital signs such as body temperature, heart rate and respiration rate. In addition, on the level of the hematology parameters; red blood cells count, hemoglobin, hematocrit, white blood cell counts, as well as on some Biochemical Parameters including total protein, albumin, urea, creatinine, bilirubin, glucose and cortisol.The results of the study showed that there were some changes associated with acupuncture sessions in Arabian horses, between the resting state (before the aquapuncture session), during the aquapuncture session (15 minutes), and after the end of the acupuncture session (30 minutes). There were significant changes (P < 0.05) in heart rate, respiratory rate, and body temperature, that increased during the acupuncture session and began to decrease after the session ended. Also, significant variables were recorded in albumin and cortisol level (P < 0.05). The highest value of albumin was seen during aquapuncture session, but the highest concentration of the cortisol level was after the end of the session. On the other hand, there were no significant variables (P ˃ 0.05) in erythrocyte and leukocytes count, hemoglobin, hematocrit, urea, creatinine, bilirubin, and glucose.
Keywords: Acupuncture – Cortisol – CBC – Arabian Horses